Method for optimizing methanation of carbon dioxide
By constructing ZnCdSe-CdS heterojunction quantum dot aerogel, the low efficiency of quantum dot photocatalysts in the carbon dioxide reduction process was solved, and efficient carbon dioxide methanation and stable catalytic performance were achieved.
Patent Information
- Application Number
- CN202510873239.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-27
- Publication Date
- 2025-10-03
AI Technical Summary
Existing quantum dot photocatalysts have problems with high recombination rate of photogenerated electron-hole pairs and difficulty in balancing band gap size with redox ability during the carbon dioxide reduction process, resulting in low efficiency. In addition, there are problems with weak inter-particle contact and insufficient lattice compatibility in the heterogeneous structure construction.
A ZnCdSe-CdS heterojunction quantum dot aerogel was constructed, and a stable fusion interface was formed through a cation-induced assembly method to optimize the carbon dioxide methanation process. The band arrangement and multi-level pore structure of ZnCdSe and CdS quantum dots were utilized to promote charge separation and transport.
It significantly improved the generation performance and selectivity of carbon dioxide methanation, enhanced the photocatalytic activity and stability, and enhanced the light absorption capacity and charge transfer efficiency.
Smart Images

Figure CN120733758A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of clean energy conversion, and in particular to a method for optimizing carbon dioxide methanation. Background Art
[0002] The excessive consumption of fossil fuels and the resulting persistent CO2 emissions are triggering a global energy and environmental crisis. With the continued growth of global energy demand and the increasing depletion of non-renewable resources, the development of clean and renewable energy technologies has become a key area of global concern. Despite progress in organic catalysts, metal complexes, metal oxides and traditional semiconductor materials, overcoming the challenges in CO2 reduction remains a research hotspot.
[0003] Quantum dots (QDs) have shown significant advantages in the field of photocatalysis due to their unique photophysical properties. However, QDs photocatalysts are still limited by the high recombination rate of photogenerated electron-hole pairs, which is mainly due to the strong Coulomb interaction between electrons and holes, resulting in a decrease in energy conversion efficiency. In addition, single-component QDs find it difficult to strike a balance between band gap size and redox ability: a larger band gap enhances redox ability but limits light absorption, while a smaller band gap improves light capture ability but may not be able to drive effective reactions.
[0004] In order to improve the performance of QD photocatalysts, constructing heterojunctions has become a key strategy to address the common efficiency bottleneck problem of single-component QDs. Heterojunctions combine the advantages of two semiconductor materials to achieve efficient photogenerated charge separation and transfer, inhibit electron-hole recombination, and thus improve photocatalytic efficiency.
[0005] However, due to the limitations of QD morphology and lattice compatibility between materials, constructing efficient heterojunctions in QD components still faces challenges. On the one hand, the spherical structure of QDs limits the effective contact between particles, resulting in weak interfacial interactions. On the other hand, the lattice mismatch between materials may affect the stability of the heterojunction and the insufficient inter-QD contact hinders interfacial charge transfer, reducing the overall photocatalytic efficiency. Therefore, the present invention proposes a method for optimizing carbon dioxide methanation to solve the problems existing in the prior art. Summary of the Invention
[0006] In response to the above problems, the purpose of the present invention is to propose a method for optimizing carbon dioxide methanation. The method for optimizing carbon dioxide methanation optimizes carbon dioxide methanation by constructing ZnCdSe-CdS heterojunction quantum dot aerogel, thereby overcoming problems such as charge recombination of quantum dot materials and thereby improving the generation performance and selectivity of CO2 methanation.
[0007] To achieve the purpose of the present invention, the present invention is implemented by the following technical solution: a method for optimizing carbon dioxide methanation, comprising the following steps:
[0008] Step 1: Construct ZnCdSe-CdS heterojunction quantum dot aerogel and ultrasonically disperse it in water. After stirring evenly, transfer it to a 25 mL Pyrex photoreactor, continuously introduce CO2 gas, and then seal the photoreactor.
[0009] Step 2: A light source simulating sunlight is arranged next to the photoreaction container, and the photoreaction container is irradiated for a long time to efficiently catalyze the reduction of CO2 to obtain methane.
[0010] Further improvements are: in step 1, the mass volume ratio of ZnCdSe-CdS heterojunction quantum dot aerogel to water is 1-5 mg:3-6 mL; after uniform dispersion, a hole sacrificial agent is added to the mixed liquid, wherein the hole sacrificial agent is triethanolamine, and the volume ratio of triethanolamine to water is 0.5-2:3-6; and the CO2 gas is introduced for 5-20 min.
[0011] A further improvement is that the ZnCdSe-CdS heterojunction quantum dot aerogel in step 1 is prepared as follows:
[0012] S1, CdS-MPA powder and Zn 0.75 Cd 0.25 Se-MPA QDs were uniformly mixed and reacted in water to form a stable precursor solution;
[0013] S2, Al 3+ introduced into the precursor solution to induce gelation;
[0014] S3, after the aging process, a mixed heterojunction gel network is formed to obtain a complete orange transparent Zn 0.75 Cd 0.25 Se-CdS QD gel quantum dot gel;
[0015] S4, washing the quantum dot gel with water, repeating multiple cycles to eliminate residues;
[0016] S5. Freeze-drying the washed ZnCdSe-CdS gel to generate heterojunction quantum dot aerogel.
[0017] Further improvement is that: the CdS-MPA powder and Zn in S1 0.75 Cd 0.25 The amount of Se-MPA QDs used was 5 mg, the amount of water used was 1 mL, and the mixing reaction time was 1 h; the Al in S2 3+ The introduction is in the form of AlCl3, and the amount of AlCl3 used is 0.02 mmol; the aging time in S3 is 2-3 days; and the washing cycle in S4 is repeated for more than 20 times.
[0018] A further improvement is that the CdS-MPA powder in S1 is prepared as follows:
[0019] The first step is to prepare CdS-OA quantum dots using the oil phase hot injection method;
[0020] The second step is to purify the CdS-OA quantum dots;
[0021] Step 3: Prepare an MPA precursor solution and vigorously mix it with CdS-OA and stir for 0.5 h. Add deionized water during the stirring process. After mixing, separate the solutions and transfer the supernatant CdS-MPA to a dark environment.
[0022] Step 4: repeatedly washing the CdS-MPA three times with dichloromethane, then adding acetone and centrifuging to obtain purified CdS-MPA dispersed in water.
[0023] Further improvement is that: Zn in S1 0.75 Cd 0.25 Se-MPA QDs were prepared as follows:
[0024] The first step is to dissolve ZnCl2 and 3-mercaptopropionic acid in deionized water to prepare a ZnCl2-MPA solution in a three-necked beaker;
[0025] Step 2: Under an N2 inert gas atmosphere, NaBH4 was used to reduce selenium powder in water to prepare a NaHSe solution, which was then added to the ZnCl2-MPA solution to obtain a mixed solution.
[0026] The third step was to heat the mixed solution to 90 °C for 1 h, stir vigorously and adjust the pH to 11.0, wait for the growth of ZnSe-MPA QDs, and then precipitate and wash with isopropanol several times and redisperse in water;
[0027] Step 4: CdCl2 solution was mixed with MPA, and ZnSe solution heated at 90°C for 30 min was added dropwise under stirring. The pH value was then adjusted to 11.0 with NaOH, and the reaction system temperature was maintained at 90°C for 2 h.
[0028] Step 5: Add a small amount of isopropanol for precipitation, repeat the precipitation and washing for more than 20 times to obtain purified Zn 0.75 Cd 0.25 Se-MPA QDs.
[0029] A further improvement is that the reactions from the first step to the fifth step are all carried out in an oxygen-free aqueous solution under N2 protection; and the temperature at which the selenium powder is heated to be completely dissolved during reduction in step 2 is 250°C.
[0030] Further improvements are: the light source in step 2 is composed of a 300W xenon lamp and a 420nm nano-cutoff filter; the light intensity in step 2 is controlled at 80-120mW / cm2, the irradiation is at a vertical angle, and the irradiation time is 4-12h.
[0031] The beneficial effects of the present invention are as follows: the present invention adopts a simple cation-induced assembly method to successfully design and prepare a hybrid heterojunction gel ZnCdSe-CdS gel composed of ZnCdSe and CdS quantum dots, and constructs a stable fusion interface to achieve efficient photocatalytic CO2 reduction;
[0032] The multi-level pore structure and high specific surface area of ZnCdSe-CdS gel provide an ideal nanocrystalline framework for adsorption process and mass transfer. The co-assembly strategy of ZnCdSe significantly enhances the light absorption capacity of CdS quantum dots and significantly improves the photocatalytic activity. 2+ Doping further optimized the light-harvesting properties of ZnCdSe-CdS gel;
[0033] In addition, since the conduction band bottom (CBM) and valence band top (VBM) of ZnCdSe quantum dots are higher than those of CdS quantum dots and they have lower charge transfer resistance, this band arrangement promotes more efficient charge separation and transport in the ZnCdSe-CdS heterojunction, thereby achieving high activity and high selectivity in the CO2 methanation reaction;
[0034] The present invention optimizes CO2 methanation through ZnCdSe-CdS gel, greatly improving the methane yield, and the ZnCdSe-CdS gel has excellent durability, excellent catalytic stability and cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 This is a diagram for evaluating the catalytic performance of the quantum dot photocatalyst of the present invention.
[0036] Figure 2 This is a high-resolution transmission electron microscope image of the present invention.
[0037] Figure 3 This is the X-ray photoelectron spectrum of the present invention.
[0038] Figure 4 This is a high-angle annular dark-field scanning transmission electron microscope and energy-dispersive X-ray spectrometer of the present invention.
[0039] Figure 5 This is a high-resolution STEM image of the present invention.
[0040] Figure 6This is a combined diagram of the Mott-Schottky test results and an analysis diagram of n-type semiconductor characteristics for the first and second comparisons of the present invention.
[0041] Figure 7 This is a diagram of the optical band gap value determined by combining DRS spectrum and Tauc curve in the present invention.
[0042] Figure 8 CdS and Zn 0.75 Cd 0.25 Schematic diagram of the energy band structure of Se.
[0043] Figure 9 Schematic diagram of the photocurrent density of the present invention.
[0044] Figure 10 This is the electrochemical impedance spectroscopy analysis diagram of the present invention.
[0045] Figure 11 The figure shows the dynamic characteristics of charge carriers and the photoluminescence test diagram of the present invention.
[0046] Figure 12 This is the TRPL attenuation curve of the present invention in H2O.
[0047] Figure 13 This is a diagram of the work function and Fermi level alignment of CdS and ZnCdSe simulated by the present invention.
[0048] Figure 14 This is the in-situ XPS measurement diagram of the present invention.
[0049] Figure 15 This is a diagram showing the catalytic performance of the ZnCdSe QDs gel in Example 3 of the present invention.
[0050] Figure 16 This is a comparison diagram of the light absorption range and catalytic activity before and after doping with Cd in the present invention.
[0051] Figure 17 This is the spectrum curve of ZnCdSe-CdS gel of the present invention.
[0052] Figure 18 This is an analysis chart of the effects of different condition deletions on the photocatalytic CO2 reduction performance in Example 4 of the present invention.
[0053] Figure 19 This is the in-situ diffuse reflectance infrared Fourier transform spectrum of the present invention.
[0054] Figure 20 This is a schematic diagram of the CO2 methanation following the formaldehyde pathway of the present invention. DETAILED DESCRIPTION
[0055] In order to deepen the understanding of the present invention, the present invention will be further described in detail below with reference to the examples. The examples are only used to explain the present invention and do not constitute a limitation on the scope of protection of the present invention.
[0056] In the following examples, a 300 W xenon lamp was used, Solaredge 700, from China; a cutoff filter λ>420 nm was used, from UQG Optics; H 2 was measured using a thermal conductivity detector (TCD), and CO and CH 4 were measured using a flame ionization detector (FID); and the gas chromatograph was a GC 7820A, using an Ar carrier, from Agilent.
[0057] Example 1
[0058] This embodiment provides a method for optimizing carbon dioxide methanation, comprising the following steps:
[0059] Step 1: Construct a ZnCdSe-CdS heterojunction quantum dot aerogel and ultrasonically disperse it in water, wherein the mass volume ratio of ZnCdSe-CdS heterojunction quantum dot aerogel to water is 1-5 mg:3-6 mL. After stirring evenly, add triethanolamine hole sacrificial agent to the mixture, and the volume ratio of triethanolamine to water is 0.5-2:3-6. Transfer it to a 25 mL Pyrex photoreactor, continue to introduce CO2 gas for 5-20 minutes, and then seal the photoreactor;
[0060] The ZnCdSe-CdS heterojunction quantum dot aerogel was prepared as follows:
[0061] S1, 5mg of CdS-MPA powder and 5mg of Zn 0.75 Cd 0.25 Se-MPA QDs were uniformly mixed and reacted in 1 mL of water for 1 h to form a stable precursor solution;
[0062] The CdS-MPA powder used was prepared as follows:
[0063] The first step is to prepare CdS-OA quantum dots by oil-phase hot injection method. Specifically, 0.128g CdO powder is mixed with 2.5mL OA and 12.5mL octadecene (ODE), and heated to 250°C until completely dissolved to obtain a precursor solution; 0.0802g S powder is added to 5ml ODE and heated to 100°C until completely dissolved to obtain a sulfur precursor solution. 1mL of the sulfur precursor solution is injected into the precursor solution to obtain a mixed solution; the mixture is reacted at 250°C under N2 protection for 30min to synthesize CdS-OA quantum dots;
[0064] In the second step, the CdS-OA quantum dots were purified by adding 25 mL of isopropanol and 4 mL of methanol to the reaction solution in the first step, mixing thoroughly, and then centrifuging at 11,000 rpm (=15,000 RCF) for 30 min; the precipitate was collected and dissolved in 6 mL of dichloromethane (DCM); then, 3 mL of acetonitrile (ACN) was added for secondary precipitation, and the resulting quantum dots were recorded as CdS-OA quantum dots;
[0065] The third step is to prepare an MPA precursor solution, specifically, taking 300 μL of 3-mercaptopropionic acid MPA, dissolving it in 1 mL of methanol, and then adjusting the pH to 10-11 with 300 μL of 60% NaOH solution (0.840 gIn 1.2 mL H2O) to obtain an MPA precursor solution, which is then vigorously mixed and stirred with 600 μL of CdS-OA for 0.5 h. Deionized water is added during the stirring process to separate the reaction solution. After mixing, the solution is separated. When the lower layer is milky white and the upper solution is clear and transparent, the supernatant CdS-MPA is transferred and stored in a dark environment;
[0066] Step 4: Repeatedly wash the CdS-MPA three times with dichloromethane to remove excess oil phase material, then add acetone and centrifuge to obtain purified CdS-MPA dispersed in 500 μL H2O;
[0067] Zn used 0.75 Cd 0.25 Se-MPA QDs were prepared as follows:
[0068] Step 1: Dissolve 0.2 mmol of ZnCl2 and 160 μL of 3-mercaptopropionic acid in 20 mL of deionized water to prepare a ZnCl2-MPA solution in a three-necked beaker;
[0069] Step 2: Under an N2 inert gas atmosphere, 0.2 mmol of selenium (Se) powder was reduced with 0.5 mmol of NaBH4 in 10 mL of water to prepare a NaHSe solution, which was then added to the ZnCl2-MPA solution to obtain a mixed solution. The temperature at which the selenium powder was reduced and heated to complete dissolution was 250°C.
[0070] The third step was to heat the mixed solution to 90 °C for 1 h, stir vigorously and adjust the pH to 11.0, wait for the growth of ZnSe-MPA QDs, and then precipitate and wash with isopropyl alcohol (IPA) multiple times and redisperse in water;
[0071] Step 4: CdCl2 solution was mixed with MPA, and ZnSe solution heated at 90°C for 30 min was added dropwise under stirring. The pH value was then adjusted to 11.0 with 1M NaOH, and the reaction system temperature was maintained at 90°C for 2 h.
[0072] Step 5: Add a small amount of isopropanol for precipitation, repeat the precipitation and washing for more than 20 times to remove excess salt and obtain purified Zn 0.75 Cd 0.25 Se-MPA QDs;
[0073] The reactions from the first step to the fifth step are all carried out in an oxygen-free aqueous solution under N2 protection;
[0074] S2, 0.02 mmol of AlCl3 was introduced into 1 mL of the precursor solution to induce gelation;
[0075] S3, after 2d aging process, a mixed heterojunction gel network is formed to obtain a complete orange transparent Zn 0.75 Cd 0.25 Se-CdS QD gel quantum dot gel;
[0076] S4, washing the quantum dot gel with water, repeating the cycle for more than 20 times to eliminate residues;
[0077] S5, freeze-drying the washed ZnCdSe-CdS gel to generate heterojunction quantum dot aerogel;
[0078] Step 2: A light source simulating sunlight is placed next to the photoreaction container and irradiated for a long time to efficiently catalyze the reduction of CO2 to produce methane;
[0079] The light source consists of a 300W xenon lamp and a 420nm nano-cutoff filter; the light intensity is controlled at 80-120mW / cm2, irradiated at a vertical angle, and the irradiation time is 4-12h.
[0080] Example 2
[0081] according to Figures 1-14 As shown, this embodiment provides a specific comparison and experimental process of the method of the present invention.
[0082] 5 mg of CdS-MPA and 5 mg of Zn 0.75 Cd 0.25Se-MPA QDs were vigorously mixed in 1 mL of water for 1 hour to form a stable precursor solution; 0.02 mmol of AlCl3 was introduced into 1 mL of the precursor solution to induce the crosslinking (gelation) of the colloidal quantum dots; and an aging process of about two days was performed to form a mixed heterojunction gel network, i.e., a complete orange transparent Zn 0.75 Cd 0.25 Se-CdS QD gel; the quantum dot gel was extensively washed with water and repeated for more than 20 cycles to eliminate any potential residues; finally, the resulting ZnCdSe-CdS gel was freeze-dried to produce quantum dot aerogel.
[0083] First comparison: Preparation of CdS QDs, 0.128g of cadmium oxide (CdO) powder was mixed with 2.5mL of oleic acid (OA) and 12.5mL of octadecene (ODE), and then the mixture was heated to 250°C until completely dissolved to obtain a precursor solution; 0.0802g of sulfur (S) powder was dispersed in 5mL of octadecene (ODE), and then heated to 100°C until the sulfur powder was completely dissolved to obtain a sulfur precursor solution, which was then injected into the precursor solution and stirred thoroughly to mix evenly, finally obtaining a uniform mixed solution; the mixed solution was placed in a N2 atmosphere, and the reaction system temperature was controlled to be constant at 250°C. Under this condition, the reaction was continued for 30 minutes, and oleic acid-stabilized CdS quantum dots were successfully synthesized.
[0084] Second comparison: Preparation of ZnCdSe QDs: 0.2 mmol of ZnCl2 and 160 μL of 3-mercaptopropionic acid (MPA) were dissolved in 20 mL of deionized water to obtain a ZnCl2-MPA solution.
[0085] Under N2 protection, 0.2 mmol of selenium (Se) powder was reduced in 10 mL of water with 0.5 mmol of NaBH4 to obtain a NaHSe solution, which was then added to the ZnCl2-MPA solution. The pH value was adjusted to 11.0 under vigorous stirring, and the mixed solution was heated to 90°C for 1 hour to initiate the growth of ZnSe-MPA QDs.
[0086] The synthesized ZnSe-MPA quantum dots were purified by multiple precipitation and washing with isopropyl alcohol (IPA) and then redispersed in water. The resulting ZnSe nanocrystal solution was heated at 90°C for 30 minutes to further stabilize its properties.
[0087] 0.1M CdCl2 solution was pre-mixed with a slightly excess of mercaptopropionic acid (MPA) and added dropwise to the ZnSe solution under continuous stirring. 1M NaOH was then used to adjust the pH of the system to 11.0. The reaction system was controlled at 90°C for 2 hours. A small amount of isopropyl alcohol (IPA) was added to precipitate the synthesized quantum dots (QDs). The QDs were then redispersed in deionized water. The precipitation and washing process was repeated several times to obtain the purified ZnSe. 0.75 Cd 0.25 Se-MPA QDs.
[0088] Third comparison: Preparation of CdS / ZnCdSe QDs: The method is the same as the first and second comparisons, except that a physical mixture of ZnCdSe and CdS QDs is used.
[0089] First experimental example:
[0090] 1. Under aqueous conditions, the photocatalytic performance of quantum dot catalysts was systematically evaluated; when tested separately, as shown in the attached instructions Figure 1 As shown in the figure, both the CdS quantum dots prepared in the first comparison and the ZnCdSe QDs prepared in the second comparison exhibited low catalytic activity. In addition, when the two quantum dots were simply physically mixed (ZnCdSe / CdS QDs) to prepare the third comparison, its catalytic activity was only comparable to the average value of the activity of the individual components, indicating that the interaction between the two components during the catalytic process was weak. However, when CdS and ZnCdSe QDs were co-assembled into a gel (ZnCdSe-CdS gel), the photocatalytic activity was significantly improved, which was mainly attributed to the co-assembly of ZnCdSe enhancing the light absorption ability of CdS QDs, and the close contact between the quantum dots promoted the separation and transfer of electron-hole pairs.
[0091] 2. As attached to the instruction manual Figure 2 This is a high-resolution transmission electron microscope (HRTEM). As shown in the figure, the CdS QDs prepared in the first comparison and the ZnCdSe QDs prepared in the second comparison both exhibit monodisperse characteristics, while the prepared ZnCdSe-CdS gel shows a stronger fusion state. The high-resolution TEM image further reveals that the interface fusion degree of ZnCdSe–CdS gel is significantly enhanced compared to single-component CdS or ZnCdSe QDs.
[0092] In addition, X-ray photoelectron spectroscopy (XPS) (see Appendix Figure 3a, b, c) analysis confirmed the coexistence of Zn, Cd, Se and S elements in ZnCdSe-CdS gel, and the combination of high-angle annular dark field scanning transmission electron microscopy (HAADF-STEM) and energy dispersive X-ray spectroscopy (EDX) (see the attached manual) Figure 4 ), further analysis revealed the uniform distribution characteristics of Se (derived from ZnCdSe) and S (derived from CdS) in ZnCdSe-CdS aerogel, as well as the formation of a well-connected network structure, and attached high-resolution STEM images (as attached to the manual) Figure 5 ) to clearly present the highly matched lattice structure and coherent interface of ZnCdSe-CdS gel to confirm. And in the process of freeze-drying to generate ZnCdSe-CdS aerogel, a multi-level porosity (1-100nm) and 195m 2 The high-surface-area quantum dot aerogel (QD) creates an optimal nanocrystalline framework for enhanced adsorption and mass transfer. This aerogel exhibits significant advantages over ZnCdSe and CdS QDs in terms of network structure, adsorption, and mass transfer, providing favorable conditions for efficient photocatalytic CO2 reduction.
[0093] 3. Instruction Manual Figure 6 The Mott-Schottky test results of the first and second comparisons are combined with the graph and the analysis of n-type semiconductor characteristics. Generally, the conduction band minimum position (CBM) of n-type semiconductors is about 0.20V negative than its Efb value. Therefore, under pH = 7, relative to NHE, CdS and ZnCdSe (Zn 0.75 Cd 0.25 The conduction band (CB) positions of Se) quantum dots are -0.63V and -1.49V respectively, both of which have sufficient reducing power to convert CO2 into CO and CH4. The optical band gap value determined by combining DRS spectrum and Tauc curve is shown in the appendix of the manual. Figure 7 The band gap of CdS and ZnCdSe is 2.43eV and 2.15eV respectively, and the corresponding valence band maximum position (VBM) is 1.80V and 0.66V respectively. 0.75 Cd 0.25 Schematic diagram of the energy band structure of Se, the results are as shown in the attached instructions Figure 8 The analysis results show that the CBM and VBM of ZnCdSe QDs are higher than those of CdS QDs. This band alignment contributes to more efficient charge separation in the ZnCdSe-CdS heterojunction, thereby optimizing the photocatalytic performance.
[0094] 4. The photocurrent response measurement shows that the photocurrent density of the ZnCdSe-CdS gel prepared above is significantly higher than that of the CdS prepared in the first comparison and the ZnCdSe gel prepared in the second comparison. The results are shown in the attached manual. Figure 9 This is consistent with its excellent photocatalytic performance. In addition, electrochemical impedance spectroscopy (EIS) analysis shows that the semicircle radius of ZnCdSe-CdS gel is significantly reduced, indicating that its charge transfer resistance is reduced and the charge transfer efficiency is improved. The results are shown in the attached manual. Figure 10 shown.
[0095] By further analyzing the dynamic characteristics of charge carriers and photoluminescence (PL) testing (see the attached manual), Figure 11 ), and found that the PL intensity of ZnCdSe-CdS gel was significantly reduced compared with that of CdS gel, indicating that radiative recombination was suppressed, which may be due to the exciton delocalization effect within the heterojunction system.
[0096] Instructions attached Figure 12 The TRPL decay curves in H₂O for the present invention, the first comparison, and the second comparison are shown. As shown, the PL decay lifetime of the ZnCdSe-CdS gel (2.1 ns) is much shorter than that of the ZnCdSe QDs (57.3 ns), indicating a significant reduction in the charge carrier lifetime. This rapid PL decay further confirms the efficient exciton delocalization process within the ZnCdSe-CdS gel, which promotes charge separation and transport, enhancing the overall photocatalytic performance.
[0097] 5. By using density functional theory (DFT) to simulate the work function and Fermi level alignment of CdS and ZnCdSe (see the attached manual) Figure 13 In addition, the plane average charge density difference at the ZnCdSe-CdS heterojunction interface was simulated, confirming the significant charge redistribution at the interface (see the attached manual). Figure 13 c). Calculations show that the surface work function of ZnCdSe is 5.12 eV, higher than the 4.81 eV of CdS. This suggests that during heterojunction formation, electrons spontaneously transfer from CdS (with a lower work function and higher Fermi level) to ZnCdSe until the Fermi level reaches equilibrium. This electron migration forms a depletion / accumulation layer at the interface, generating a strong internal electric field (IEF), further promoting charge separation and transport.
[0098] Under visible light irradiation, the built-in electric field follows the Type-Ⅱ band alignment mechanism, driving the photogenerated electrons to migrate from the conduction band minimum (CBM) of ZnCdSe to the CBM of CdS (see the attached manual). Figure 13 d). This electron transfer pathway was further verified by in-situ XPS measurement (see Appendix Figure 14 a, b) The measurement results show that the photogenerated electrons in ZnCdSe transfer to CdS and actively participate in the subsequent photocatalytic reaction. These findings further confirm the electron transport mechanism of the ZnCdSe-CdS heterojunction during the photocatalytic process and provide theoretical support for its efficient photocatalytic performance.
[0099] Furthermore, during XPS measurements, when the ZnCdSe-CdS aerogel sample was exposed to visible light, the binding energies of Zn 2p and Se 3d shifted positively by +0.12 eV and +0.1 eV, respectively, while the binding energy of Cd 3d shifted negatively by -0.12 eV, also indicating that photogenerated electrons were transferred from ZnCdSe to CdS. This result further validates the photogenerated charge transfer properties of the ZnCdSe-CdS heterojunction and provides strong evidence for its efficient electron separation and transfer mechanism in photocatalytic applications.
[0100] Example 3
[0101] according to Figure 15 、 Figure 16 and Figure 17 As shown, this embodiment provides a specific comparison and experimental process of the method of the present invention.
[0102] A ZnCdSe QDs gel with a Zn:Cd ratio of 0.75:0.25 was prepared.
[0103] Fourth comparison: ZnCdSe QDs gel with Zn:Cd=0.85:0.15.
[0104] Fifth comparison: ZnCdSe QDs gel with Zn:Cd=0.60:0.40.
[0105] Second experimental example:
[0106] 1. Studies have shown that the Zn:Cd ratio has an important influence on catalytic performance. By adjusting the Cd content in ZnCdSe QDs (0%–40%), the absorption spectra of the ZnCdSe QDs gel with Zn:Cd = 0.75:0.25 were compared and the catalytic performance showed a "volcanic" trend (see the attached manual). Figure 15 ).
[0107] 2. As attached to the instruction manual Figure 16 As shown in a, b, and c, appropriate amount of Cd doping helps to broaden the light absorption range and enhance the catalytic activity. 2+ As the doping amount increases from 0% to 25%, the light absorption of ZnCdSe gradually redshifts, thereby enhancing the light capture ability of ZnCdSe-CdSgel.2+ With the increase of doping level, the band gap of ZnCdSe gradually narrows. However, excessive Cd doping may reduce the conduction band position of ZnCdSe QDs, thereby reducing the electron injection efficiency of CdS QDs. After measuring the Cd content by EDS, it was found that Zn 0.75 Cd 0.25 Se-CdS aerogel has the best catalytic performance, with its CH4 generation rate increased by 12 times compared with the original CdS gel.
[0108] 3. In addition, the effect of the mass ratio of ZnCdSe to CdSQDs on the photocatalytic CO2 reduction performance was also explored. The results of mass ratio optimization showed that when the ZnCdSe 0.75 Cd 0.25 Under the Se loading, the CH4 production reached the maximum value (240.4 μmol·g -1 ·h -1 ), the selectivity is 76%, and the apparent quantum yield (AQY) is 1.2% under 400nm light. Figure 17 As shown in Figure 2, the AQY of ZnCdSe-CdS gel under single wavelength irradiation of 400nm, 450nm, 500nm and 550nm is consistent with the UV-vis absorption spectrum. However, after further increasing the ZnCdSe content to 67%, the catalytic activity decreased, which may be attributed to:
[0109] (1) Excessive ZnCdSe QDs limit the light absorption capacity of CdS;
[0110] (2) The interaction between ZnCdSe-CdS QDs is weakened, hindering the electron transfer efficiency.
[0111] Overall, the performance of ZnCdSe-CdS gel in CO2 methanation is better than most reported heterojunction catalysts based on CdS materials, showing broad application prospects.
[0112] Example 4
[0113] according to Figure 18 、 Figure 19 and Figure 20 As shown, this embodiment provides a specific comparison and experimental process of the method of the present invention.
[0114] The method for constructing ZnCdSe-CdS heterojunction quantum dot aerogel to optimize carbon dioxide methanation includes the following steps:
[0115] 2 mg of ZnCdSe-CdS heterojunction quantum dot aerogel catalyst was uniformly dispersed in deionized water by ultrasonic dispersion, followed by the addition of 1 mL of triethanolamine (TEOA) as a hole sacrificial agent. After thorough stirring and mixing, the mixed solution was transferred to a 25 mL Pyrex photoreactor. High-purity CO2 gas was then continuously introduced into the reactor under dark conditions for 20 minutes to fully expel air from the system, and the system was then sealed with a rubber septum.
[0116] A 300W xenon lamp (Solaredge 700, China) was used as the light source, and a 420nm cutoff filter (λ>420nm, UQG Optics) was used to simulate sunlight to ensure that the incident light power density was maintained at 100mW cm -2 , then, the photoreactor is continuously irradiated to achieve efficient photocatalytic CO2 reduction reaction;
[0117] After 5 h of continuous illumination, 1 mL of product gas (containing CH4, CO, and H2) was collected and quantitatively analyzed using a gas chromatograph (GC-9790IIGC, Fuli). H2 was detected by a thermal conductivity detector (TCD), and CO and CH4 were determined by a flame ionization detector (FID).
[0118] Sixth comparison: The method is the same as the above method, except that argon (Ar) is used to replace CO2, and the other conditions and parameters are carried out according to Example 3.
[0119] Seventh comparison: The method was the same as the above method, except that TEOA was not added, and other conditions and parameters were the same as those in Example 3.
[0120] The eighth comparison is the same as the above method, except that the xenon lamp and the cutoff filter device are replaced by a dark environment, and the other conditions and parameters are the same as those in Example 3.
[0121] Ninth comparison: The method is the same as the above method, except that the ZnCdSe-CdS heterojunction quantum dot aerogel is not added, and the other conditions and parameters are the same as those in Example 3.
[0122] The third experimental example:
[0123] 1. Instruction Manual Figure 18 The effects of different condition deletions on the photocatalytic CO2 reduction performance in Example 3 and the sixth to ninth comparisons are shown.
[0124] It can be seen that the generation of CH4 and CO comes from the photocatalytic CO2 reduction of ZnCdSe-CdS gel.
[0125] Specifically, only a small amount of H2 was generated under Ar atmosphere, while no reduction products were detected under no light conditions, and the yields of carbon-based products in both groups of experiments were close to zero, indicating that the carbon products originated from the photocatalytic CO2 reduction process.
[0126] Furthermore, the yield of the reduction product was significantly decreased in the TEOA-free system, confirming the importance of TEOA as a hole sacrificial agent in the catalytic reaction.
[0127] At the same time, no gas products were detected under catalyst-free conditions, further proving that the catalyst plays a key role in the generation of carbon products.
[0128] 2. Instruction Manual Figure 19 The results of in situ diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS) were used to characterize the intermediate species formed during the CO2 reduction process on ZnCdSe-CdS quantum dot aerogel catalyst. The results showed that as the irradiation time increased, the ZnCdSe-CdS aerogel sample at 1570 cm -1 The absorption peak intensity at 2078 cm gradually increases, which is attributed to the accumulation of COOH* intermediates. -1 The absorption peak at 1112 cm -1 (CH3O*) and 1460cm -1 The new absorption band at (CHO*) further indicates that CO2 methanogenesis follows the formaldehyde pathway (see the attached manual). Figure 20 shown).
[0129] Based on the results of in situ DRIFTS experiments, a plausible photocatalytic reaction mechanism for ZnCdSe-CdS gel was proposed. First, CO2 molecules adsorbed on the ZnCdSe-CdS gel surface were reduced to COOH* intermediates by photogenerated electrons. These intermediates then further combined with electrons and protons to generate CO*. The strongly adsorbed CO* then underwent further, stepwise reduction to form CHO and CH3O, ultimately generating methane. This process demonstrates that the strong adsorption of the CO* intermediate plays a key role in the CO2 methanation reaction.
[0130] Combined with the analysis of the photocatalytic mechanism, the proposed mechanism includes three enhancement strategies:
[0131] (1) Optimized charge dynamics via a Type-II heterojunction, where photogenerated electrons are rapidly transferred from ZnCdSe to CdS, thanks to the intimate interfacial contact within the aerogel;
[0132] (2) The aggregation of quantum dots in the gel matrix enhances the CO2 adsorption capacity, promotes the transfer of electrons to the surface-bound CO2 molecules, and drives the subsequent reduction reaction;
[0133] (3) The abundant nanocrystalline interfaces of QD aerogels promote the generation of hydrogen protons, providing an ample source of protons for the reduction of CO2 to methane. This synergistic effect of charge separation and reactant activation gives the system excellent photocatalytic performance.
[0134] The basic principles, main features, and advantages of the present invention are shown and described above. Those skilled in the art should understand that the present invention is not limited to the foregoing embodiments. The foregoing embodiments and descriptions are merely illustrative of the principles of the present invention. Various changes and modifications may be made to the present invention without departing from the spirit and scope of the present invention. Such changes and modifications are intended to fall within the scope of the present invention. The scope of protection claimed in the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for optimizing carbon dioxide methanation, characterized in that: The following steps are involved: Step 1: Construct ZnCdSe-CdS heterojunction quantum dot aerogel and ultrasonically disperse it in water. After stirring evenly, transfer it to a 25 mL Pyrex photoreactor, continuously introduce CO2 gas, and then seal the photoreactor. Step 2: A light source simulating sunlight is arranged next to the photoreaction container, and the photoreaction container is irradiated for a long time to efficiently catalyze the reduction of CO2 to obtain methane.
2. The method for optimizing carbon dioxide methanation according to claim 1, characterized in that: In the step 1, the mass volume ratio of ZnCdSe-CdS heterojunction quantum dot aerogel to water is 1-5 mg:3-6 mL; after uniform dispersion, a hole sacrificial agent is added to the mixed solution, wherein the hole sacrificial agent is triethanolamine, and the volume ratio of triethanolamine to water is 0.5-2:3-6; the CO2 gas is introduced for 5-20 min.
3. The method for optimizing carbon dioxide methanation according to claim 1, wherein: The ZnCdSe-CdS heterojunction quantum dot aerogel in step 1 is prepared as follows: S1, CdS-MPA powder and Zn 0.75 Cd 0.25 Se-MPA QDs were uniformly mixed and reacted in water to form a stable precursor solution; S2, Al 3+ introduced into the precursor solution to induce gelation; S3, after the aging process, a mixed heterojunction gel network is formed to obtain a complete orange transparent Zn 0.75 Cd 0.25 Se-CdSQD gel quantum dot gel; S4, washing the quantum dot gel with water, repeating multiple cycles to eliminate residues; S5. Freeze-drying the washed ZnCdSe-CdS gel to generate heterojunction quantum dot aerogel.
4. The method for optimizing carbon dioxide methanation according to claim 3, characterized in that: The CdS-MPA powder and Zn in S1 0.75 Cd 0.25 The amount of Se-MPA QDs used was 5 mg, the amount of water used was 1 mL, and the mixing reaction time was 1 h; the Al in S2 3+ The introduction is in the form of AlCl3, and the amount of AlCl3 used is 0.02 mmol; the aging time in S3 is 2-3 days; and the washing cycle in S4 is repeated for more than 20 times.
5. The method for optimizing carbon dioxide methanation according to claim 3, characterized in that: The CdS-MPA powder in S1 was prepared as follows: The first step is to prepare CdS-OA quantum dots using the oil phase hot injection method; The second step is to purify the CdS-OA quantum dots; Step 3: Prepare an MPA precursor solution and vigorously mix it with CdS-OA and stir for 0.5 h. Add deionized water during the stirring process. After mixing, separate the solutions and transfer the supernatant CdS-MPA to a dark environment. Step 4: repeatedly washing the CdS-MPA three times with dichloromethane, then adding acetone and centrifuging to obtain purified CdS-MPA dispersed in water.
6. The method for optimizing carbon dioxide methanation according to claim 3, characterized in that: Zn in S1 0.75 Cd 0.25 Se-MPA QDs were prepared as follows: The first step is to dissolve ZnCl2 and 3-mercaptopropionic acid in deionized water to prepare a ZnCl2-MPA solution in a three-necked beaker; Step 2: Under an N2 inert gas atmosphere, NaBH4 was used to reduce selenium powder in water to prepare a NaHSe solution, which was then added to the ZnCl2-MPA solution to obtain a mixed solution. The third step was to heat the mixed solution to 90 ° C for 1 h, stir vigorously and adjust the pH value to 11.0, wait for the growth of ZnSe-MPAQDs, and then precipitate and wash with isopropanol multiple times and redisperse in water; Step 4: CdCl2 solution was mixed with MPA, and ZnSe solution heated at 90°C for 30 min was added dropwise under stirring. The pH value was then adjusted to 11.0 with NaOH, and the reaction system temperature was maintained at 90°C for 2 h. Step 5: Add a small amount of isopropanol for precipitation, repeat the precipitation and washing for more than 20 times to obtain purified Zn 0.75 Cd 0.25 Se-MPA QDs.
7. The method for optimizing carbon dioxide methanation according to claim 6, characterized in that: The reactions from the first step to the fifth step are all carried out in an oxygen-free aqueous solution under N2 protection; the temperature at which the selenium powder is heated to be completely dissolved during the reduction in the second step is 250°C.
8. The method for optimizing carbon dioxide methanation according to claim 1, characterized in that: The light source in step 2 is composed of a 300W xenon lamp and a 420nm nano-cutoff filter; the light intensity in step 2 is controlled at 80-120mW / cm2, the irradiation is at a vertical irradiation angle, and the irradiation time is 4-12h.